Religious, Poetic and Argumentative Persuasion in the Helen of Gorgias - Rutten, Emanuel (NTT, 2023)
What does Gorgias has to say about religious speech considered as a form of rhetorical speech directed at persuasion? Or more precisely, what does his rhetoric teaches us about the nature and origin of the persuasiveness of religious speech? Now, to properly understand how, according to Gorgias, from a rhetorical perspective religious beliefs arise, this article shall first deal with his conception of the connection between language, thinking and being. And for this purpose, it will consider his treatise On the Non-Existent or On Nature—after which it shall engage with his rhetorical interpretation of religious speech in the Helen. In this way it becomes clear wherein lies the power of religious speech and what it means for the way in which people are religiously convinced and come to religious faith.